Hyperglycemia Augmented Neuropathic Pain Involving the HMGB1/TLR4 Inflammatory Axis - Cheng-Yi Chang; Ping-Ho Pan; Tzu-Hsuan Liu; Chih-Cheng Wu; Chih-Jen Hung; Wen-Ying Chen; Su-Lan Liao; Yu-Fang Chen; Chun-Jung Chen (Tungs’ Medical Journal, 2022)
Peripheral neuropathy, accompanied by chronic neuropathic pain, is among the frequent and debilitating complications of diabetes. Hyperglycemia is a risk factor for neuropathic pain, but the pathological mechanisms are unclear. The high mobility group box 1 (HMGB1)/toll-like receptor 4 (TLR4) inflammatory axis is strongly implicated in the pathogenesis of neuropathic pain, so we examined how hyperglycemia influences the HMGB1/TLR4 axis and behavioural manifestations of hyperalgesia in the Sprague-Dawley rat sciatic nerve chronic constriction injury (CCI) model. Short-term hyperglycemia induced by streptozotocin significantly augmented mechanical allodynia and thermal hyperalgesia in CCI model rats compared to normoglycemic CCI model rats. These augmented nociceptive behaviours were associated with increased immune cell infiltration and activation, cytokine production and expression levels of TLR4 and HMGB1, as well as with reduced Sirt1 expression in spinal cord dorsal horn and sciatic nerve. High glucose also enhanced HMGB1/TLR4 inflammatory axis activity and cytokine production in lipopolysaccharide-stimulated RAW264.7 macrophages. Our results suggest that hyperglycemia predisposes individuals with peripheral nerve injury to neuropathic pain, in part through enhancement of Sirt1/HMGB1/TLR4 signalling and ensuing neuroinflammation.